The Use of Synectic Learning Models in Improving Student Learning Creativity in Catholic Religious Education Subjects at Graphic Bina Media Vocational High School Medan - Erikson Simbolon; Wina Alfionita Saragih; Paulinus Tibo (Indonesian Journal of Educational Science and Technology, 2023)
This research is to determine the learning creativity of students by using a synectic learning model. The location chosen by the author for this research is at SMK Graphic Bina Media Medan. This study uses a qualitative method. The data obtained from this study are in the form of primary data and secondary data. Data analysis used in this study is data reduction, data presentation and conclusion. Data collection techniques in this study were interviews, observation and documentation. There were 15 informants in this study consisting of 1 school principal, 1 PAK teacher, 3 fellow teachers and 10 students. The findings of this study are that the learning creativity of students has increased by using the synectic model. This can be seen from the implementation of the 5 model requirements such as: syntax, social system, reaction principle, interactional impact and support systems as well as the implementation of 4 indicators of creativity such as: fluency of thinking, flexibility thinking, elaboration, and originality.